Đề xuất mô hình quản lí hoạt động phát triển năng lực nghiên cứu khoa học của giảng viên trẻ tại các trường đại học - Trần Huy Hoàng, Trần Huy Hoàng; Nguyễn Lê Vân An; Phạm Thảo Ngọc, Phạm Thảo Ngọc (Tạp chí Giáo dục, 2026)
As universities place greater emphasis on strengthening research competence and developing academic staff capable of sustaining long-term research engagement, early-career lecturers require support appropriate to their career stage, experience, collaborative networks, and level of professional autonomy. Drawing on a focused theoretical review, this article proposes a model for managing research competence development activities for early-career lecturers at universities. The findings identify three theoretical foundations: functional management, communities of practice, and human resource development. The model illustrates the relationships among institutional orientations and conditions, management actors at university and faculty levels, a four-step management cycle, research communities, competence development activities, expected outcomes, and feedback mechanisms. Within the model, the direct object of management is the system of competence development activities, while progress in task performance and increasing autonomy are considered important outcomes alongside research outputs. The article contributes to the theoretical basis for organizing, supporting, and evaluating the development of research competence among early-career lecturers at universities.